SLOBODAN SELENIĆ’S ANTHOLOGICAL WORK (Philological Studies, 2025)
This paper explores the anthological work of Slobodan Selenić, with a focus on two key anthologies – Avant-Garde Drama (1964) and Anthology of Contemporary Serbian Drama (1977). The starting point is the assumption that Selenić, through his selection and theoretical framing of dramatic texts, shaped the criteria for studying 20th-century Serbian dramatic literature. The study emphasizes that Selenić’s theoretical thought is not only reflected in his books Engagement in Dramatic Form and Dramatic Trends of the 20th Century, but also in the prefaces to the anthologies, which reveal his sensitivity to both the historical and contemporary dimensions of theater. The aim of the paper is not to provide a comprehensive analysis of Selenić’s anthological principles, but rather to synthesize the most important theoretical insights found in the anthologies' prefaces. The paper highlights Selenić’s ability to combine his practical experience as a critic with a systematic theoretical approach to drama, and underlines the importance of these anthologies as valuable sources for studying his dramatic and theatrical thought, especially within the context of the chronological development of Serbian drama.
Keywords: Slobodan Selenić, anthology, dramatic literature, avant-garde drama, Serbian theater, dramatic trends